A RIDDle solved: Why an intact IRE1α/XBP‐1 signaling relay is key for humoral immune responses. (20th February 2014) - van, Eelco; Orsi, Andrea; Sitia, Roberto
<x xml:space="preserve">Abstract</x> As they commit to plasma cell differentiation, B lymphocytes must swiftly gear up to produce and secrete huge amounts of antibodies. To develop their secretory capacity, B cells exploit a signaling pathway that is employed by all eukaryotic cells in response to endoplasmic reticulum stress. An article by Benhamron et al. in this issue of the European Journal of Immunology, [Eur. J. Immunol. 2014. 44: 867–876] sheds new light on why an intact IRE1/XBP‐1 signaling relay is central to orchestrate the full‐blown expansion of the secretory machinery needed for massive antibody production